Explicit Dynamic DDA Method considering Dynamic Contact Force - Jian Zhao; Ming Xiao; Juntao Chen; Dongdong Li (Shock and Vibration)
This paper proposes an explicit dynamic DDA method considering dynamic contact force, which aims at solving the problems of low efficiency of dynamic contact detection and the simulation of dynamic contact force in the conventional DDA method. The mutual contact between blocks can be regarded as the application of point loading on a single block, and the corresponding contact submatrix can be calculated and the simultaneous equations of the block system can be integrated. The central difference method is adopted to deduce the explicit expression of block displacement containing dynamic contact force. With the relationship between displacement and dynamic contact force, contact constraint equations of a block system are obtained to calculate the dynamic contact force and the corresponding block displacement. The accuracy of the explicit dynamic DDA method is verified using two numerical cases. The calculation results show that the new DDA method can be applied in large-scale geotechnical engineering.